SYNTAXONOMY AND NOMENCLATURE OF THE ALPINE HEATHS (THE CLASS LOISELEURIO-VACCINIETEA) IN THE WESTERN CARPATHIANS - ŠIBÍK, Jozef; KLIMENT, Ján; JAROLÍMEK, Ivan; DÚBRAVCOVÁ, Zuzana; BĚLOHLÁVKOVÁ, Radmila; PACLOVÁ, Libuše (Hacquetia, 2015)
The article refers to the syntaxonomical revision of plant communities of the class Loiseleurio-Vaccinietea from the territory of the Western Carpathians. This class relates to alpine and subalpine heathlands of Eurasia mountain systems dominated by ericaceous species. All available relevés were analysed using the numerical approach. The floristic and ecological characteristics of the associations are given, and the relationships with allied syntaxa are discussed. Analysed communities are divided into two alliances, the Loiseleurio-Vaccinion, and the Vaccinion myrtilli. Within these alliances, a new association (Sphagno capillifolii-Empetretum nigri), and subassociations (Cetrario islandicae-Vaccinietum vitis-idaeae typicum and empetretosum nigri, Cetrario nivalis-Vaccinietum gaultherioidis typicum and empetretosum nigri, Hylocomio splendentis-Vaccinietum vitis-idaeae vaccinietosum gaultherioidis and dianthetosum nitidi, Sphagno capillifolii-Empetretum nigri typicum and luzuletosum alpinopilosae) are described. The authors also highlight far less known valid names of the associations Cetrario islandicae-Vaccinietum vitis-idaeae and Avenastro versicoloris-Vaccinietum myrtilli (incl. Vaccinietum myrtilli), validate the names of the associations Cetrario nivalis- Vaccinietum gaultherioidis and Junco trifidi-Callunetum, and propose a new name for the association Vaccinio-Empetretum nigri on calcareous bedrocks (Hylocomio splendentis-Vaccinietum vitis-idaeae).